MINAT JUAL BELI ONLINE SHOP MASYARAKAT MENURUT HUKUM BISNIS ISLAM - Ummairah Batubara; Nahar Alang Abdul Ghani (MUTLAQAH: Jurnal Kajian Ekonomi Syariah, 2022)
This research is motivated by the assumption that buying and selling interest will greatly affect a business or online shop when a business or online shop they use provides good service and provides satisfaction to consumers. against consumers, from delivering defective products to fraud. This research was conducted in the Department of Islamic Economics, Faculty of Islamic Religion, Islamic University of North Sumatra. The population is 100 people, the sample is taken by accidental sampling, namely the technique of determining the sample based on chance if it is considered that the person who happened to be met is suitable as a data source, totaling 30 students. Data collection techniques through observation, interviews, questionnaires, and documentation.The researcher analyzed the data by using quantitative descriptive method by conducting statistical tests. To analyze the data, the researcher used research instrument test, classical assumption test and hypothesis test. From the results of this study, it was found that the relationship between online shop buying and selling interest on Islamic business law was 0.683, which was strong. And the coefficient of determination is 0.434. This means that the contribution given by the interest variable to customer satisfaction is 43.4% while the remaining 56.6% is influenced by other variables that are not in this study. And the view of Islamic economics regarding the variable of buying and selling interest is appropriate, because based on the verse of the Koran QS An-Nisa '/4: 29, Buyers carry out buying and selling (commerce) with online shops based on consensual, also have a contract that was agreed at the beginning. And achieve the target of customer satisfaction.